Brazil Modernizes its Armed Forces - Salgado Defranc, Eddy José (2012)
What are the reasons why Brazil has decided to modernize the country's Armed Forces and what implications would this have for the region, are some of the questions that this essay aims to answer, conducting a study of the policies implemented by the last rulers to make a follow-up of its actions in this area, as well as the investment made in this area and the weapons potential that the country would currently have.